Applications of variational methods to some three-point boundary value problems with instantaneous and noninstantaneous impulses - Wei, Yongfang; Shang, Suiming; Bai, Zhanbing (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we study the multiple solutions for some second-order p-Laplace differential equations with three-point boundary conditions and instantaneous and noninstantaneous impulses. By applying the variational method and critical point theory the multiple solutions are obtained in a Sobolev space. Compared with other local boundary value problems, the three-point boundary value problem is less studied by variational method due to its variational structure. Finally, two examples are given to illustrate the results of multiplicity.
Keywords: three-point BVPs; variational method; critical point theory; multiple solutions; noninstantaneous impulse